STRIKES WITHOUT THE UNION’S PRESENCE AND UNION REPRESENTATION: LEGAL FRAMEWORK AND COURT’S UNDERSTANDING IN BRAZIL: marco jurídico e entendimento dos tribunais no Brasil - Martinucci Boldrin, Paulo Henrique (2023)
The present work aims to analyze whether strikes without the union’s presence are influenced by the union representation of workers foreseen in the current model of Brazilian union organization. The research was based on an empirical study of jurisprudence and adopted benchmarks of analysis of content of decisions issued by Brazilian labour courts (Tribunais Regionais do Trabalho – TRT’s and Tribunal Superior do Trabalho - TST) that dealt with these striking movements. As a result, it was possible to verify the presence of indications that workers’ union representation in the Brazilian model of union organization is a determining factor for strikes without the union’s presence, especially due to the lack of instruments that allow the measurement of the unions' representativeness.